Undercover wolf - Tyler, Paige (Tyler, Paige. STAT, Special Threat Assessment Team, 2021)
"When an international security threat emerges in Paris, alpha werewolf Harley Grant and the Special Threat Assessment Team lead the investigation. Harley is hesitant to use her wolf abilities, but she's sure she smells the work of a supernatural suspect. She soon finds she's not the only alpha on the scene. The MI6 joins STAT, eager to help squash the insurgents. But agent Sawyer Bishop has a secret--he's a werewolf. He would give anything to work openly, like the intriguing STAT she-wolf, but his MI6 teammates' complicated history with non-humans holds him back. As both teams run out of time, they have no other choice. Harley can no longer deny her wolf, and Sawyer can no longer hide his."--Page 4 of cover.